CMV‐infected kidney grafts drive the expansion of blood‐borne CMV‐specific T cells restricted by shared class I HLA molecules via presentation on donor cells. Issue 8 (3rd March 2018) - Gatault, Philippe; Al‐Hajj, Sally; Noble, Johan; Chevallier, Eloi; Piollet, Marie; Forconi, Catherine; Gaudy‐Graffin, Catherine; Thibault, Gilles; Miquelestorena‐Standley, Elodie; Halimi, Jean‐Michel; Büchler, Matthias; Lemoine, Roxane; et al.
Abstract : We aimed to determine the role of cytomegalovirus (CMV)‐infected donor cells in the development of a CMV‐specific immune response in kidney transplant recipients. We assessed the CMV pp65‐specific immune response by using interferon‐ɣ ELISPOT and dextramers in peripheral blood mononuclear cells from 115 recipients (D+R− 31, D+R + 44, D−R + 40) late after transplantation (mean 59 ± 42 months). Receiving a kidney from a D+ donor resulted in a higher number of IFN‐ɣ‐producing anti‐CMV T cells ( P  = .004). This effect disappeared with the absence of shared HLA class I specificities between donors and recipients ( P  = .430). To confirm the role of donor cells in stimulating the expansion of newly developed CMV‐specific CD8 + T cells after transplantation, we compared the number of HLA‐A2–restricted CMV‐specific CD8 + T cells in primo‐infected recipients who received an HLA‐A2 or non–HLA‐A2 graft. The median of anti‐CMV pp65 T cells restricted by HLA‐A2 was very low for patients who received a non–HLA‐A2 graft vs an HLA‐A2 graft (300 [0‐14638] vs. 17972 [222‐85594] anti‐CMV pp65 CD8 + T cells/million CD8 + T cells, P  = .001). This adds new evidence that CMV‐infected kidney donor cells present CMV peptides and drive an inflation of memory CMV‐specific CD8 + T cells, likely because of frequent CMV replications within the graft. Abstract : Donor cytomegalovirus (CMV) infection affects the CMV‐specific immune response and donor‐shared HLA‐I is crucial for the development of CMV‐specific CD8+ T cells, suggesting that CMV‐infected kidney donor cells present CMV peptides and drive an inflation in memory CMV‐specific T cells.